Quality of financial disclosures related to environmental, social, and governance matters, and firm characteristics and firm value: A comparative study across four ASEAN countries - Putri, Nadya Aprilia; Pratama, Arie (International Journal of Management and Sustainability, 2023)
This research aims to understand how a company’s characteristics influence its disclosure of sustainability-related financial information and how such disclosure affects the company’s value. The study uses three company characteristics as variables: size, profitability, and leverage. The two dependent variables are the quality of sustainability reporting and company value. The research uses a quantitative explanatory method. The study uses sustainability disclosure data, based on the IFRS S1 framework, from 162 companies listed on the sustainability-based stock indexes in Indonesia, Malaysia, Singapore, and Thailand in 2021. The data obtained were analyzed using descriptive statistical analysis and path analysis. The study results show that only company size influences the quality of sustainability item disclosure, while profitability and leverage have no effect. The quality of sustainability item disclosure has a positive effect on company value. This study shows that sustainability disclosure in financial reports can increase a company’s value in the eyes of investors, but significant efforts are still needed to improve the quality of such disclosure. The findings indicate that the size of a firm has a significant impact on the expenses associated with publishing sustainability information. However, the company’s performance does not have a similar relationship.